(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
Standards of audit have been defined issued them by professional organizations the audit risk is: Failure of the auditor inadvertently to amend his opinion on the financial statements in suitable method, although these statements are Interpolated Essentially. As result the deep impacts caused by electronic operating systems in the accounting data in the audit process which audit risk has gained attention of many professional sides, especially the audit process and quality is relating with level of discovery the auditor for the mistakes of origin (misrepresentations) all their types and give the necessary confidence for the auditor to express his technical opinion in fidelity and certified financial statements which prepared electronically. According to the international standard of audit No. 400 and it’s characterized by risk assessment and internal audit, the risks defined by the International Federation of Accountants (IFAC) they are the risk of misinformation that occurs in account balance or set of transactions that can be Material alone or when combined them with incorrect transactions in other assets or groups which cannot be prevented, detected and corrected them only by the accounting system or internal audit systems opportunely. These risks and challenges that face the accounts auditor were very necessary to keep pace with developments in information technology and they can be able express his technical opinion neutrally in the financial statements. From this point, our research have included four sections focused on the risk of audit job and the possibility of reducing these risks to minimum, and we have reached set of conclusions and recommendations serving auditors and other entities for working purposes professionally to get the efficiency and quality of the audit job.